DEVELOPMENT OF WORDWALL GAMES TO IMPROVE LITERACY AND NUMERACY IN EARLY CHILDHOOD 5-7 YEARS OLD - Siti Alifah Faiz; Herpratiwi; Dwi Yulianti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Literacy and numeracy skills are the main foundation for early childhood education, which plays a role in preparation for the next level of education. The purpose of this research is to develop educational games based on digital technology such as wordwall to improve early childhood literacy and numeracy skills. This research uses the Research and Development (R&D) method using a development research design based on the ADDIE model. The trials in this study were carried out in two ways, namely media expert trials and material trials at Khalifah Kindergarten, Jati Agung South Lampung. The results of the study indicate that the effectiveness of wordwall based educational games in improving literacy and numeracy skills among young children stems from the fact that this medium offers interactive, visual, and game based learning that aligns with children’s learning characteristics. These findings suggest that the use of interactive digital learning media not only enhances learning outcomes but also creates meaningful learning experiences tailored to the developmental stages of young children. The results theoretically, this study reinforces the concept of digital game-based learning in early childhood education, while practically, it offers an innovative alternative for teachers to enhance the quality of learning, making it more active, enjoyable, and meaningful.